Characterization of a Multispectral Imaging System Based on Narrow Bandwidth Power LEDs - Tamayo Monsalve, Manuel A.; Osorio, Gustavo; Liliana Montes, Nubia; López, Santiago; Cubero, Sergio; Blasco, José (IEEE Standards Association, 2021)
Multispectral imaging systems using narrow-band power LEDs have become a feasible solution for a wide range of applications. Their fast response and simple implementation compensate for a low spectral resolution. In this article, we are filling a gap identified in the literature on multispectral systems by presenting a detailed design of a light controller, as well as a characterization of the whole system by means of a correlation and a repeatability analysis. We use a reference color target to assess accuracy and precision by comparing our system with high-performance hyperspectral equipment used in fruit quality control. The system captures multispectral images (MSIs) with 15 different wavelengths (λ ∈ [410 950] nm). The main finding is a Pearson correlation index above 80% (ρ > 0.8) with a variance in the measure within 10% (σ 2 <; 0.1). We also examine the characteristics of the instrument at a maximum speed of 8 MSIs/s although this entails sacrificing precision (σ 2 <; 0.3).